ANALISIS PENGARUH TQM TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan PT. Rimatex Putra Nusantara Wanarejan Taman, Pemalang) - Amarullah, Idris; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2017)
TQM or Total Quality Management is a management strategy shown to instill a quality awareness on all processes within the organization. In accordance with the ISO definition, TQM is